An Interview with Fulvio Caccia - Melfi, Mary (Italian Canadiana, 2024)
In this interview, Fulvio Caccia, an Italian-Canadian Governor General’s Award–winning francophone poet, novelist, and essayist, reflects on his literary career spanning over four decades. A prolific writer who has published over two dozen books, Caccia discusses the underlying themes in his works and the unique challenges posed by different literary forms. Caccia acknowledges that he often explores themes of identity and belonging in his creative endeavours, readily unravelling the layers of the immigrant experience. In his search for self-discovery, he challenges conventional notions of nationality and cultural belonging. A Montrealer at heart, but now living in the Paris region, Caccia delves into the genesis of his novel, La coïncidence (Triptyque, 2005), which focuses in part on the École Polytechnique massacre, a mass shooting that occurred on the grounds of the University of Montreal on 6 December 1989, killing fourteen female engineering students and injuring many others. In the narrative, the author looks into the enduring impact of past traumas on present lives, the complexities of human relationships, and the interplay of fate, love, and tragedy. Beyond a mere discussion of this novel, which was translated from French into English by Robert Richard and published by Guernica Editions in 2015, Caccia offers in this interview profound insights into his poetry, which draws extensively from his experiences as the son of Italian immigrants.